Push and pull factors influencing visitors to Putrajaya Wetland Park - Omar, Mohd Azlizairi (2018)
Motivation plays a vital role in people live especially when it comes to time of making a decision. The motivation in decision making helps to reveal the factors influencing people choice of activities and their preferred recreational area during their leisure time. This study was conducted at Putrajaya Wetland Park. A total of 140 questionnaires was distributed to the visitors during weekends and school holidays in the month of March 2018. This study finds significant factors influencing participation of visitors such as to spend holiday and to enjoy the natural scenery. The research findings provide further understanding on people needs and wants for their recreational activities where it is useful to the related agency for their future management purposes.